(untitled) (Journal of the Sociology and Theory of Religion, 2018)
Since the Charlie Hebdo attacks in January 2015, Islamophobia has continued to increase among all areas of society: education, access to employment and housing and in the participation in public affairs. The two Supranational European Courts, both the Court of Justice of the European Union (CJEU) and the European Court of Human Rights (ECHR) have also been influenced by the general tendency, more and more pronounced, of rejection towards "the Muslim". In the first part, this article will analyze the concept and manifestations of the term "Islamophobia" in Europe. The second part will examine how the two Supranational European Courts have justified some limitations to the manifestation of religious freedom, particularly on Muslim women, by relying on Islamophobic prejudices.